zien, denken, schilderen : een gesprek met Roger Raveel. - Deboutte, Melanie (Machelen-aan-de-Leie : Roger Raveel Museum, 2021)
Raveel, Roger ; Verdegem, Jos ; Spilliaert, Léon ; Brusselmans, Jean ; Malfait, Hubert ; Burssens, Jan ; Léger, Fernand ; Permeke, Constant ; De Smet, Léon ; De Smet, Gust ; Van Severen, Dan ; De Keyser, Raoul ; Van Gogh, Vincent
zien, denken, schilderen. een gesprek met Roger Raveel, Roger Raveel Museum, Machelen-aan-de-Leie, 28.03 - 18.07.2021
boek